STRATEGI PENGEMBANGAN PROFESIONAL GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DALAM KURIKULUM MERDEKA: STUDI LITERATUR - Putri Kirani; Siti Nurkhasanah Rusmiono; Achmad Muhtadin; Ikmawati (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
The Strategy of Teacher Professional Development to Improve Learning Quality in the Merdeka Curriculum is motivated by the uneven distribution of teacher competencies in curriculum implementation, which affects the quality of learning. This study aims to analyze the role of teacher professional development, identify effective strategies, and explain its contribution to innovative and student-centered learning. This research uses a library research method by analyzing ten relevant scientific articles obtained from Google Scholar and SINTA-indexed journals published between 2023 and 2026. Data were analyzed through data reduction, thematic classification, descriptive presentation, and conclusion drawing. The findings indicate that teacher professional development plays a significant role in improving pedagogical and professional competencies, particularly in designing differentiated instruction, developing authentic assessment, and managing adaptive classrooms. Effective strategies include continuous practice-based training, collaboration through learning communities and teacher forums, reflective practices, and the integration of technology. Therefore, teacher professional development should be designed systematically, contextually, and sustainably to support the successful implementation of the Merdeka Curriculum.